2020
DOI: 10.3390/ijerph17176320
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Healthcare Needs and Associated Factors in Rural and Suburban Vietnam: A Cross-Sectional Study

Abstract: The purpose of this study was to examine the current utilization of healthcare services, exploring unmet healthcare needs and the associated factors among people living in rural Vietnam. This cross-sectional study was conducted with 233 participants in a rural area. The methods included face-to-face interviews using a structured questionnaire, and anthropometric and blood pressure measurements. We considered participants to have unmet health needs if they had any kind of health problem during the past 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“… 19 However, in a study of the general population in Viet Nam, BMI was not found to be associated with unmet healthcare needs. 20 Further research is needed to better understand the association between BMI and unmet healthcare needs. However, one possible explanation is that overweight older people face a complex interaction of body systems due to aging process and several comorbidities, 21 such as hypertension, diabetes, and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 19 However, in a study of the general population in Viet Nam, BMI was not found to be associated with unmet healthcare needs. 20 Further research is needed to better understand the association between BMI and unmet healthcare needs. However, one possible explanation is that overweight older people face a complex interaction of body systems due to aging process and several comorbidities, 21 such as hypertension, diabetes, and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants lived in rural locations, had limited education and low incomes. In Vietnam, the healthcare system has many challenges such as the shortage of community-based (primary care) medical doctors, the overload of patients, the tendence for people to value tertiary hospitals in large cities, and the financial cost of healthcare for most of the population [ 52 ]. These factors lead to a reduced frequency of healthcare seeking and insufficient health information provided by hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…While people in the urban benefit directly from health facilities for the elderly, more than 70% of Vietnamese elderly live in rural areas, where limited financial resources are available, 30 and thus have difficulties with accessing health services. 31 Since elderly people with depression are especially vulnerable to barriers of mental health services, we propose that the interventions should target these seniors. Depression may be an important indicator of the need for formal and informal community and home care of mental health services.…”
Section: Discussionmentioning
confidence: 99%